2012
DOI: 10.1142/s0219519412400179
|View full text |Cite
|
Sign up to set email alerts
|

Novel Classification of Coronary Artery Disease Using Heart Rate Variability Analysis

Abstract: Coronary artery disease (CAD) is a leading cause of death worldwide. Heart rate variability (HRV) has been proven to be a non-invasive marker of the autonomic modulation of the heart. Nonlinear analyses of HRV signals have shown that the HRV is reduced significantly in patients with CAD. Therefore, in this work, we extracted nonlinear features from the HRV signals using the following techniques: recurrence plots (RP), Poincare plots, and detrended fluctuation analysis (DFA). We also extracted three types of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
3
32
1
1
Order By: Relevance
“…Their work obtained an accuracy of 79.71% using 18 principal components. In [77], the nonlinear features from the heart rate signals are extracted using recurrence plots, Poincare plots, DFA, Shannon entropy, approximation entropy, and sample entropy to automatically detect CAD patients. These features after PCA have yielded a classification accuracy of 89.5% using multilayer perceptron (MLP) classifier using eight principal components.…”
Section: Resultsmentioning
confidence: 99%
“…Their work obtained an accuracy of 79.71% using 18 principal components. In [77], the nonlinear features from the heart rate signals are extracted using recurrence plots, Poincare plots, DFA, Shannon entropy, approximation entropy, and sample entropy to automatically detect CAD patients. These features after PCA have yielded a classification accuracy of 89.5% using multilayer perceptron (MLP) classifier using eight principal components.…”
Section: Resultsmentioning
confidence: 99%
“…Patidar et al presented a new method for diagnosis of CAD using tunable-Q wavelet transform based features extracted from heart rate signals [49]. Many linear and nonlinear parameters are extracted from heart rate signals and used as diagnostic features to predict the subjects with CAD [3][4][5][6], the features were then fed into classifiers for automated diagnosis of CAD subjects [4][5][6]. In our previous publication, we have reported the univariate analysis results for RRI and DTI (analysis of RRI is also performed in this study, the results are shown in Table S1 in supplementary materials), using sample entropy, fuzzy entropy, and refined fuzzy entropy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have studied the linear and nonlinear features of HRV for different positions (e.g., the supine, left lateral and right lateral positions), and the features were fed into classifiers for the purpose of classifying normal and coronary artery disease (CAD) states in previous studies [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One field of study that the use of recurrence plot is relatively common is the analysis of biological signals. Some examples are the analysis of electrocardiograms [34], electroencephalograms [9] and electromyograms [15], [30], as well detection of coronary artery disease [13].…”
Section: Related Workmentioning
confidence: 99%